Personal branding for early-career professionals: the challenges for absolute beginners - Gomes, Cesar Alexandre Silva Rivas (2024)
The study focuses on addressing the main challenges early career professionals face when starting to manage their professional brands as they enter a corporate context post business bachelor’s degree. Through a semi structured in-depth interviews method, the work draws on prior personal/professional branding and sociological field theory to understand the challenges stated above. Moreover, it analyzes how changes are perceived necessary in online and offline personal positioning, the main variables that affect the intensity of these challenges and conducive practices to mitigating those tensions to enhance professional branding while maintaining personal identity. The findings of the study may give a clear theoretical and managerial understanding to the main key stakeholders involved in the process, such as students, universities, and employers.